2015
DOI: 10.1371/journal.pone.0127844
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Human Valve Interstitial Cell Phenotype and Function Using a Fibroblast Growth Factor 2 Formulation

Abstract: Valve interstitial cells (VICs) are fibroblastic in nature however in culture it is widely accepted that they differentiate into a myofibroblastic phenotype. This study assessed a fibroblast culture media formulation for its ability to maintain the phenotype and function of VICs as in the intact healthy valve. Normal human VICs were cultured separately in standard DMEM and in fibroblast media consisting of FGF2 (10ng/ml), insulin (50ng/ml) and 2% FCS for at least a week. Cell morphology, aspect ratio, size, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
82
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(90 citation statements)
references
References 38 publications
8
82
0
Order By: Relevance
“…Latif et al published a full rationale for the selection of the cocktail present in FIB media. 11 Briefly, supplementation with 2% FBS was selected over the traditional 10% concentration to reduce the amount of growth factors present in the medium. In addition, insulin and FGF-2 were selected for their reported ability to regulate growth 18 and decrease VIC aSMA expression, 19 respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Latif et al published a full rationale for the selection of the cocktail present in FIB media. 11 Briefly, supplementation with 2% FBS was selected over the traditional 10% concentration to reduce the amount of growth factors present in the medium. In addition, insulin and FGF-2 were selected for their reported ability to regulate growth 18 and decrease VIC aSMA expression, 19 respectively.…”
Section: Discussionmentioning
confidence: 99%
“…14,20,21 Our experiments found that collagen coating alone can decrease the expression of contractile proteins but significantly increases VIC proliferation and thus is unable to yield a qVIC phenotype ( Figure S6); others have similarly found that collagen is not sufficient to yield qVIC cultures. 11,14 We hypothesized, however, that the combination of a collagen coating with soluble factors (ie, FIB-Coll condition) might provide additional deactivation cues. This hypothesis was confirmed by the data: Although the FIB formulation alone was sufficient to generate significant reductions in myofibroblast markers, culture in FIB-Coll achieved the same results, sometimes sooner (4 versus 9 days for ECM production) and at other times more dramatically (eg, proliferation and apoptosis), compared with FIB alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We further characterized the differences between normal and diseased hVICs by quantifying mRNA expression of key VIC markers including VIM (qui escent VIC marker 43 ), α - SMA (activated VIC marker 43 ), RUNX - 2 and OPN (osteoblastic VIC marker 44 ). Compared to the normal hVICs, both diseased hVICs demonstrated higher RUNX - 2 and OPN levels, while showing similar mRNA levels of VIM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TGF-β3 has demonstrated antifibrotic activity in vivo [89], and elevated TGF-β3/TGF-β1 ratios have been associated with scarless healing phenotypes including those of oral mucosa [90] and those induced by tattooing [91]. In human valvular interstitial cells, which are of mesenchymal origin and are largely myofibroblastic in phenotype, addition of exogenous FGF2 reduced cell area, contractile activity, and a host of myofibroblast markers and deposition of ECM proteins [92]. Valvular interstitial cells demonstrate a classical activation response to TGF-β, and it has been reported that FGF2 has the ability to impede this TGF-β response in an ERK-dependent manner, likely via a decrease in SMAD-driven promoter activity through inhibition of SMAD3 nuclear accumulation [93].…”
Section: Fgf2 Antagonizes Contractile Phenotypes and Myofibroblast DImentioning
confidence: 99%